Laser sintering of silver-palladium ink for on-demand manufacturing of electronics for space applications - Ellie Schlake; Sagar Kumar Verma; Nirmala Kandadai (Scientific Reports)
Abstract Printing technology has been designated as a useful method for in-space manufacturing (ISM) of electronics. A low-power payload method is necessary for sintering printed electronics in space. This work investigates laser sintering as a viable option for ISM. Specifically, we present our work on laser sintering silver-palladium (AgPd) on rigid alumina substrates for developing liquid conductivity sensors for water reclamation processes for low Earth orbit applications. The laser sintering parameters are laser wavelength, power, and scanning speed. The laser systems studied are continuous wave lasers at 445 nm, 808 nm, 915 nm, and 1064 nm, as well as a pulsed fs laser with a 1040 nm wavelength. The laser powers tested for each continuous wave laser are limited to 1–6 W, and 0.1–1 W for the fs laser, due to the laser systems’ power limitations. The scanning speed range tested is 0.1–1 mm/s. The 445 nm laser is determined to work most efficiently at sintering AgPd, resulting in a maximum increase in conductivity from 100 to 8.9 × 105 S/m. Comparatively, the maximum conductivities achieved by the 808 nm, 915 nm, 1064 nm, and fs lasers are 3.1 × 105, 2.1 × 105, 4.1 × 105, and 1.1 × 101 S/m, respectively. Additionally, the results of all the laser systems are compared to those of furnace-sintered and thermally dried samples through their surface morphology and conductivity. The furnace-sintered and thermally dried AgPd resulted in maximum conductivities of 3.0 × 106 and 2.1 × 104 S/m, respectively. A data-driven model employing the transient heat transfer approach is developed using a licensed version of COMSOL Multiphysics 6.2. The simulation study supports the experimental laser sintering results, and the underlying physics is discussed.